2001
DOI: 10.1523/jneurosci.21-21-08505.2001
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Differentiation during Migration of Dopaminergic Progenitor Cells to the Olfactory Bulb

Abstract: A possible source for transplantable neurons in Parkinson's disease are adult olfactory bulb (OB) dopamine (DA) progenitors that originate in the anterior subventricular zone and reach the OB through the rostral migratory stream. We used adult transgenic mice expressing a lacZ reporter directed by an 8.9 kb tyrosine hydroxylase (TH) promoter to investigate the course of DAergic differentiation. Parallel transgene and intrinsic TH mRNA expression occurred during migration of DA interneurons through the mitral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
90
0
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 74 publications
12
90
0
1
Order By: Relevance
“…3C). These findings may reflect those reported in another study, in which cells in the OB granule layer also were subdivided into two populations based on their ability to become dopaminergic neurons (Baker et al, 2001). Cells in the deep layer (gr d ) did not express dopaminergic markers.…”
Section: Discussionsupporting
confidence: 86%
“…3C). These findings may reflect those reported in another study, in which cells in the OB granule layer also were subdivided into two populations based on their ability to become dopaminergic neurons (Baker et al, 2001). Cells in the deep layer (gr d ) did not express dopaminergic markers.…”
Section: Discussionsupporting
confidence: 86%
“…Given the potential clinical importance of dopaminergic cell production from adult progenitors (Baker et al, 2001), we investigated Pax6 expression patterns during adult SVZ neurogenesis. We found that Pax6 was expressed in most proliferating SVZ progenitors but only in a subpopulation of migrating neuroblasts, indicating that migrating neuroblasts are molecularly heterogeneous.…”
Section: In Pax6mentioning
confidence: 99%
“…Neuronal differentiation of SVZ neuroblasts initiates early during radial migration and passes through a unique sequence of events involving the expression of neurotransmitter receptors and rate-limiting enzymes in neurotransmitters biosynthesis (Baker et al, 2001;Carleton et al, 2003). For instance, the transcription of the tyrosine hydroxylase gene occurs in SVZ newly generated cells before they attain their final periglomerular position (Baker et al, 2001;Saino-Saito et al, 2004).…”
mentioning
confidence: 99%